Rancangan radio frequency identification (rfid) smart door lock system berbasis internet of things untuk manajemen membership fitness center - Azhar Jauharul Umam; Deni Setiana; Aditya Pradana (Computer Science and Information Technology, 2023)
The Fitness Center is a sports facility that provides a variety of sports equipment. Typically, fitness centers offer membership packages to their visitors and manually check the membership status of visitors each time they come to the fitness center. This is the basic motivation for this research, to build a system where membership packages are automatically checked. The Internet of Things (IoT) facilitates fitness center owners in managing member data and controlling who is allowed to enter the fitness area. This research utilizes RFID technology with the MFRC522 module as an access control for the fitness room, and Raspberry Pi as a microprocessor to process RFID data using Python. Member data can be managed in a web-based application using the MERN stack, as it is a popular combination for modern web application development. The research method used is Research and Development, where extensive research is initially conducted on the requirements and design of this system. Then, the implementation process is carried out both from the application side and the devices used. The research resulted in an IoT-based smart door lock system that can automatically check the membership status of visitors using RFID technology as access control. This system is IoT-based, allowing member data to be managed anywhere through the application as long as the Raspberry Pi and the device running the application are connected to the internet. The response time of this device in processing data on RFID cards/tags is an average of 177,44ms from the 60 cards/tags tested. Based on these results, it can be concluded that the built RFID smart door lock system is functioning well.